A Competência em informação na formação do arquivista: uma proposta de disciplina. - SANTOS, Evelyn de Nazaré Oliveira dos (2022)
This study aims to propose the insertion of the Information Literacy discipline as mandatory curriculum content in undergraduate courses in Archival Science in Brazil, in order to complement the archivist's education and performance, specifically in the development of skills to deal with information, both personally and professionally. The research was developed through Bibliographic Research on Information Literacy and Archival Teaching and Documentary Research in the Curriculum Guidelines of the Archival Science Course. The result of the research presents the objectives of the course, with the expected abilities, knowledge and skills of the student, and to- gether with the analysis between the theoretical elements of Archival Science, and the Actions of Information Literacy, the contents of the Information Literacy discipline are idealized to meet the difficulties in the daily practices of the student and the future professional. It is concluded that the course meets the requirements of all Brazilian courses for the best qualification of the archivist and his appreciation as a professional.